2015
DOI: 10.1614/ws-d-14-00188.1
|View full text |Cite
|
Sign up to set email alerts
|

Acetolactate Synthase–Inhibitor–Resistant Yellow Nutsedge (Cyperus esculentus): I—Phenotypic Differences

Abstract: Acetolactate synthase (ALS) -inhibitor resistance has been recently documented in a yellow nutsedge biotype in Arkansas rice production, with a target-site mutation resulting in an amino acid substitution from Trp574 to Leu. Preliminary observations have indicated that the resistant biotype showed distinct phenotypic characteristics. Two greenhouse experiments were conducted on the resistant biotype in comparison with three susceptible standards (1) to understand differential growth habit and spatial distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Flowering and Seed Production. Similar to previous observations (Bagavathiannan et al 2015), the Res biotype flowered during the 12-wk period under each of the photoperiod treatments. When Sus plants from each biotype were harvested, no floral structures were observed and none of these plants formed involucral leaves and axillary inflorescence.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Flowering and Seed Production. Similar to previous observations (Bagavathiannan et al 2015), the Res biotype flowered during the 12-wk period under each of the photoperiod treatments. When Sus plants from each biotype were harvested, no floral structures were observed and none of these plants formed involucral leaves and axillary inflorescence.…”
Section: Resultssupporting
confidence: 87%
“…This can be due to a tendency for the Res biotype to produce longer rhizomes and more tertiary daughter plants to aggressively colonize habitats. Bagavathiannan et al (2015) showed greater overall production of biomass in the Res biotype under ample space and greater potential for rapid spread relative to Sus biotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations